2017
DOI: 10.1002/slct.201601460
|View full text |Cite
|
Sign up to set email alerts
|

N‐Bromosuccinimide Promoted Direct Thiolation of Imidazoheteroaryl C‐H bonds with Disulfides

Abstract: A one‐pot protocol has been demonstrated for the regioselective sulfenylation of imidazoheterocycles with disulfides. In this method, thiols are converted to sulfenyl bromides and reacted with 2‐phenylimidazo [1, 2‐a] pyridines. This simple procedure is highly capable for sulfenylation with readily available starting materials in good to excellent yields under transition metal and base free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Regioselective C‐3 sulfenylation of imidazo[1,2‐ a ]pyridines has been extensively explored until recently with hypervalent iodine reagents, [140–145] strong acidic conditions, [146] ionic liquids, [147] NCS ( N ‐chlorosuccinamide) [148] and NBS [149] . Very recently, Adimurthy et al [150] .…”
Section: Sulfenylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Regioselective C‐3 sulfenylation of imidazo[1,2‐ a ]pyridines has been extensively explored until recently with hypervalent iodine reagents, [140–145] strong acidic conditions, [146] ionic liquids, [147] NCS ( N ‐chlorosuccinamide) [148] and NBS [149] . Very recently, Adimurthy et al [150] .…”
Section: Sulfenylationmentioning
confidence: 99%
“…[139] TBHP is proposed to dissociate into t-butoxide radical (43 A) and hydroxyl radical in presence of visible light followed by single electron transfer to afford t-butoxide radical (43 A) and hydroxide anion, which reacts further with benzenesulfinic acid (122) Regioselective C-3 sulfenylation of imidazo[1,2-a]pyridines has been extensively explored until recently with hypervalent iodine reagents, [140][141][142][143][144][145] strong acidic conditions, [146] ionic liquids, [147] NCS (N-chlorosuccinamide) [148] and NBS. [149] Very recently, Adimurthy et al [150] reported a catalyst-free approach for C-3 sulfenylation of imidazo[1,2-a]pyridines. Continuing their efforts towards developing more enviornment viable methodologies, Rahaman and co-workers [151] have reported a metal-free, photocatalyst mediated, CDC protocol for the regioselective C-3 sulfenylation of imidazo[1,2-a]pyridines (13) using thiols ( 9) as sulfenylating reagent.…”
Section: Visible Light Induced Sulfenylationmentioning
confidence: 99%
See 1 more Smart Citation
“…A plausible mechanism is illustrated in Scheme 17. Initially, disulfides 2 reacts with I 2 to generate an elecro In 2017, Meshram group [27] developed the N-bromosuccinimide promoted direct sulfenylation of imidazole-fused heterocycles with disulfides. A wide range of heterocycles and disulfides were tested, and the desired sulfenylated imidazo compounds were obtained in good to high yields in the presence of inexpensive NBS.…”
Section: Scheme 15 Sulfenylation Of Imidazo[15-a]quinolines With Dismentioning
confidence: 99%
“…18 Many elegant formylation processes have been developed for the sulfenylation at C3 of imidazo [1,2-a]pyridines. [19][20][21][22][23][24][25][26][27][28] However, there is no report on iron-catalyzed sulfenylation of imidazo[1,2-a]pyridine derivatives with thiols.…”
mentioning
confidence: 99%